2003
DOI: 10.1183/09031936.03.00102002
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cells modulate eosinophil surface markers and mediator release

Abstract: Migration from blood to tissue modulates eosinophil function, possibly through interactions with endothelial cells.The effects of contact with and migration through endothelial cells on eosinophil expression of surface markers and release of leukotriene C 4 were evaluated.A small proportion (2.6%) of eosinophils spontaneously migrated through endothelial cell monolayers. Activation of endothelial cells by interleukin (IL)-4 or IL-1b slightly increased this migration (to 12.4%), which became much greater when a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 46 publications
1
36
0
Order By: Relevance
“…51 53 This may be due to a redundancy in function of MMPs. Redundancy of MMP activity for neovascularization and hematopoietic stem cell mobilization was recently demonstrated in vivo by using MMP-9 knockout (KO) mice, MMP-2 KO mice, and double KOs.…”
Section: Discussionmentioning
confidence: 99%
“…51 53 This may be due to a redundancy in function of MMPs. Redundancy of MMP activity for neovascularization and hematopoietic stem cell mobilization was recently demonstrated in vivo by using MMP-9 knockout (KO) mice, MMP-2 KO mice, and double KOs.…”
Section: Discussionmentioning
confidence: 99%
“…CD11b/CD18 can also mediate a constitutive low-level adhesion of VCAM-1 and supports adhesion and transmigration together with a4b1 [40]. Interaction of CD11b with its ligands on endothelial cells can also induce activation of eosinophils, as shown by CD11b-dependent CD69 up-regulation on eosinophils [44]. In its function as complement receptor 3, CD11b can support eosinophil degranulation [45].…”
Section: Discussionmentioning
confidence: 99%
“…The first is the direct induction of apoptosis of CD4 + T cells and eosinophils in airways. Previous studies revealed that those activated T cells or eosinophils expressing high levels of CD69 are susceptible to spontaneous apoptosis in vitro (Matsumoto et al, 1998;Luttmann et al, 1999;Dallaire et al, 2003;Esplugues et al, 2003;Lewkowich et al, 2005;Wang et al, 2006). This pro-apoptotic effect of CD69 might be explained by the observation that CD69 is associated with the N-terminal fragment of calreticulin, a known apoptosis-inducing signal molecule (Vance et al, 2005).…”
Section: Fig 6 Effect Of Anti-cd69 Mab On Ova-induced Ahrmentioning
confidence: 99%